Impact of measurement error on predicting population-based inpatient glucose control - George E Saulnier; Janna C Castro; Curtiss B Cook (Future Science OA)
Aim: Instrument measurement error (ME) may affect ability of damped trend analysis to forecast inpatient glycemic control. Materials & methods: A statistical approach was developed to introduce ME into damped trend analysis algorithm. Point-of-care blood glucose device data were extracted from the laboratory system. Forecasts were generated from various inpatient subgroups and time intervals. Results: ME produced differences in damped trend model during the forecast learning cycle. However, forecast trajectory stayed identical regardless of ME in 85% (119/140) of studied scenarios. Forecasts did not change with greater ME. Conclusion: ME inherent in the point-of-care blood glucose device had little effect on trajectory of damped trend exponential forecasts and apparently would not influence decision making in inpatient glycemic control algorithms.